The Contribution of Agricultural Activities to Rural Development in Upper Saiss and the Challenges to its Sustainability: A Case Study of the Matmata and Bouhlo Municipalities (Taza Province, Morocco) during the Period 2020-2024 - Ghmimed, Fatima; El-Fazziki, Mohamed; El-Bazoui, Jaouad; Bouberria, Abdelouahed (Journal of Humanities & Social Sciences, 2024)
Activities to rural development in the Upper Saiss region, focusing on the sustainability challenges, through a case study of the Matmata and Bouhlo municipalities during the period 2020-2024. The study employed a descriptive geographical approach, utilizing field data collection and analysis. Results indicate that agricultural activities, particularly cereal cultivation and livestock breeding, play a crucial role in improving household incomes, with 66% of households in Matmata and 42% in Bouhlo relying primarily on agriculture for their livelihoods. However, the sector faces significant challenges, including climatic fluctuations, weak infrastructure, and fragmented land ownership. The findings also reveal that the limited irrigated areas—only 6% in Matmata and 13% in Bouhlo—hamper productivity improvement. The study recommends enhancing irrigation techniques, promoting agricultural cooperatives, and simplifying land tenure processes to develop the sector and ensure its sustainability.
Keywords: Agricultural activities; rural development; Upper Saiss; climatic challenges; land ownership; cooperatives